Relationship between the size composition observed from the photosedimention technique and chromaticity of the fine-grained surface sediments from the modern lakes, Songnen Plain. Issue 1 (1st October 2022) - Su, Yangxin; Zhang, Xinrong; Zhang, Shun; Fang, Shi; Fu, Xiuli; Shao, Hongjun
Abstract: The relationship between clay particle size in fine-grained sediments and the enrichment of organic matter and the redox degree of their environment is conducive to the judgment and evaluation of the hydrocarbon generation potential of fine-grained sediments. The grain size characteristics of clay particles in the surface fine-grained sediments of Chaersen lake, Delong lake, Hongyuan lake, Lamasi lake, and Zhongnei lake in Songnen Plain are revealed by light sedimentation method. On the basis of the test, the relationship between the particle size of clay particles and the sediment chromaticity is analyzed, and the directivity of chromaticity to the content of organic matter and redox degree of fine-grained sediments is used for the organic content estimation. It is confirmed that the particle size of clay is negatively correlated with its organic matter content and positively correlated with its redox degree. This has important reference significance for discussing the hydrocarbon generation potential and evaluation of Cretaceous lacustrine fine-grained source rocks in the Songliao Basin.